2011
DOI: 10.1155/2011/940827
|View full text |Cite
|
Sign up to set email alerts
|

NF-kB Expression in IgA Nephropathy Outcome

Abstract: Abstract. Some studies have demonstrated the involvement of nuclear factor-kappa B (NF-kB) in the pathogenesis of glomerulonephritis. The aim of our study was twofold: (1) to analyze the prognostic value of NF-kB expression in primary IgA nephropathy (IgAN) and (2) to compare the results of NF-kB expression by immunohistochemistry (IHC) and southwestern histochemistry (SWH). We analyzed 62 patients diagnosed with IgAN from 1987 to 2003. We used monoclonal antibodies to CD68 and mast cell tryptase and polyclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Activation of the NF-κB pathway has been implicated in the acceleration and progression of IgAN [16], [31]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Activation of the NF-κB pathway has been implicated in the acceleration and progression of IgAN [16], [31]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…We determined the positive effects of infliximab administration on tubular structure, being enhanced dose-dependently. In a previous study, the expressions of NF-kB were shown to increase due to nephropathy (Silva et al, 2011). In another study, NF-kB was shown to be excessively activated in renal tubular cells following tubular damage (Nguyen et al, 2014).…”
Section: Page 12 Of 34mentioning
confidence: 91%
“…The NF-κB/TLR4 pathway is well-known for regulating immunological response [19]. Evidence has indicated that the NF-κB/TLR4 pathway activity is markedly increased in IgAN patients, and that the level of the NF-κB/TLR4 pathway is associated with poorer outcomes of IgAN patients [20,21]. As an immunosuppressant, TAC downregulates the NF-κB/TLR4 pathway in a protection effect in transplantation and IgAN patients [2224].…”
Section: Discussionmentioning
confidence: 99%